Low bone mineral density linked to colorectal adenomas: a cross-sectional study of a racially diverse population - Gowda, Shilpa; Lipka, Seth; Davis-Yadley, Ashley H.; Shen, Huafeng; Silpe, Jeffrey; White, Andy; Satler, Sam; Luebbers, Dustin; Statler, James; Zheng, Anna; Elder, Joshua; Abraham, Albin; et al. (Journal of Gastrointestinal Oncology; Vol 6, No 2 (April 13, 2015): Journal of Gastrointestinal Oncology, 2015)
Background: Epidemiologic studies suggest that lower bone mineral density (BMD) is associated with an increased risk for colorectal adenoma/cancer, especially in postmenopausal women. The aim of this study is to investigate the association between osteopenia and/or osteoporosis and colorectal adenomas in patients from a New York community hospital. Methods: We performed a cross-sectional observational study on 200 patients who underwent screening colonoscopies and bone density scan (dual-energy X-ray absorptiometry) at Nassau University Medical Center from November 2009 to March 2011. Among these, 83 patients were identified as osteoporosis (T score of −2.5 or below) and 67 were osteopenia (T score between −1.0 and −2.5). Logistic regression model was performed to assess the association between osteopenia and/or osteoporosis and colorectal adenomas. Results: Among the patients with osteopenia and osteoporosis, the mean ages were 59.1 years [standard deviation (SD) =8.9] and 61.5 (SD =8.9), respectively. There were 94.0%, 85.1% and 74.7% women, respectively, in normal BMD, osteopenia and osteoporosis groups. The prevalence of colorectal adenomas was 17.9% and 25.3% in the osteopenia and osteoporosis groups, respectively, and 18.0% in the normal BMD group. After adjustment for potential confounders including age, sex, race, body mass index (BMI), tobacco use, alcohol use, history of diabetes, hypertension, or dyslipidemia, osteoporosis was found to be associated with presence of colorectal adenomas more than 2, compared to the normal BMD group. No significant associations were found for the prevalence, size, and location of adenomas. Conclusions: Our study suggests that osteoporosis is significantly associated with the presence of multiple colorectal adenomas. Prospective studies with a larger sample size are warranted in the future.